Absorption, metabolism and excretion of cobimetinib, an oral MEK inhibitor, in rats and dogs. (2nd January 2017) - Takahashi, Ryan H.; Ma, Shuguang; Yue, Qin; Kim-Kang, Heasook; Yi, Yijun; Ly, Justin; Boggs, Jason W.; Fettes, Alec; McClory, Andrew; Deng, Yuzhong; Hop, Cornelis E. C. A.; Khojasteh, S. Cyrus; et al.
Abstract: 1. The absorption, metabolism and excretion of cobimetinib, an allosteric inhibitor of MEK1/2, was characterized in mass balance studies following single oral administration of radiolabeled ( 14 C) cobimetinib to Sprague–Dawley rats (30 mg/kg) and Beagle dogs (5 mg/kg). 2. The oral dose of cobimetinib was well absorbed (81% and 71% in rats and dogs, respectively). The maximal plasma concentrations for cobimetinib and total radioactivity were reached at 2–3 h post-dose. Drug-derived radioactivity was fully recovered (∼90% of the administered dose) with the majority eliminated in feces via biliary excretion (78% of the dose for rats and 65% for dogs). The recoveries were nearly complete after the first 48 h following dosing. 3. The metabolic profiles indicated extensive metabolism of cobimetinib prior to its elimination. For rats, the predominant metabolic pathway was hydroxylation at the aromatic core. Lower exposures for cobimetinib and total radioactivity were observed in male rats compared with female rats, which was consistent to in vitro higher clearance of cobimetinib for male rats. For dogs, sequential oxidative reactions occurred at the aliphatic portion of the molecule. Though rat metabolism was well-predicted in vitro with liver microsomes, dog metabolism was not. 4. Rats and dogs were exposed to the two major human circulating Phase II metabolites, which provided relevant metabolite safety assessment. In general, the extensive sequential oxidative metabolism in dogs, and not the aromatic hydroxylation in rats, was more indicative of the metabolism of cobimetinib in humans.